Immediate effects of talocrural joint mobilization on ankle mobility, balance, and alignment in chronic ankle instability - Sim, H. S.; Ham, M. H.; Park, D. Y.; Park, S. Y.; Park, E. S.; Kim, B. H. (Korean Journal of Sport Biomechanics, 2025)
Objective: The purpose of this study was to examine the immediate effects of Maitland Grade IV talocrural joint mobilization with posterior talar glide against tibia. Method: A total of 21 healthy adults in their 20s participated in this study and received joint mobilization. Based on the Foot and Ankle Ability Measure (FAAM) for Activities of Daily Living (ADL) and Sports (S), participants were classified into 10 individuals with chronic ankle instability (CAI) and 11 healthy controls. Measurements were taken before and after mobilization, including standing rearfoot angle (SRA), dorsiflexion range of motion (DFROM), navicular drop (ND), the Star Excursion Balance Test (SEBT), the Y-Balance Test (YBT). Within-group and between-group differences in pre- and post-intervention values were analyzed. Results: After joint mobilization, both the CAI and control groups showed significant improvements in DFROM and SEBT posterior and posteromedial reach distances (p < .05). The CAI group exhibited additional significant improvements in SEBT posterolateral and medial directions, while the control group showed significant enhancements in SEBT anterior, anterolateral, and YBT anterior and posterolateral directions (p < .05). Conclusion: Maitland Grade IV posterior talar glide mobilization increased the dorsiflexion range of motion and improved balance performance in both CAI and healthy individuals. However, the control group demonstrated greater improvements in anterior dynamic stability, whereas the CAI group showed significant changes only in the posterolateral and medial directions. These findings suggest that CAI patients may have compensatory movement patterns that limit immediate structural adaptations, indicating the need for further research on long-term effects and broader clinical applications.